Differentiated reactions to Payment for Ecosystem Service Programs in the Columbia River Basin: a qualitative study exploring irrigation district characteristics as local common-pool resource management institutions in Oregon, USA. Issue 1 (April 2018) - Plumb, Spencer Thomas; Paveglio, Travis; Jones, Kelly West; Miller, Brett Alan; Becker, Dennis R
Payment for Ecosystem Services (PES) programs are increasingly employed to encourage individual actors to preserve and/or restore environmentally beneficial instream flows in freshwater ecosystems. However, the success of these PES programs has been mixed across geographic locations and the influence of local resource management institutions remains unclear. In the western U.S.A. little is known about the role of irrigation districts regarding these water transactions. This study addresses that deficit by using existing knowledge about common-pool resource management characteristics to explore the role of irrigation districts in PES programs that incentivize water transactions in the state of Oregon. We conducted 20 semi-structured interviews with irrigation district managers and water transaction experts across the state in order to identify characteristics that influenced differential adoption of market-based PES programs for water. Our results reveal three groups of districts based on: rule formation, physical infrastructure, and user homogeneity. These groupings provide a means of categorizing institutional interactions and outcomes that correspond with district adaptability to water transactions. Specifically, we identify congruence between local conditions and rules as well as investment in infrastructure as design principles that shape how irrigation district managers responded to market-based PES.